Metode Pendekatan Tafsir Kontekstual Prespektif Fazlur Rahman - Kholifatin, Luluk Indah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study aims to analyze Fazlur Rahman's contextual interpretation method, known as the